Variational circular treemaps for interactive visualization of hierarchical data - Haisen Zhao; Lin Lu (IEEE Pacific Visualization Symposium, 2015)
Visualization of hierarchical data is of great importance in information visualization. We present variational circular treemaps with a novel layout algorithm by solving disk packing as a continuous optimization problem. Our variational circular treemaps achieve higher space utilization ratio compared with the traditional circular treemaps and support natural interactions as focus+context distortions and drill-down and roll-up operations for data navigation. Experimental results show the effectiveness of our method for visualization and interaction.